Modern technologies of soldering, providing increased strength and ductility of metal joints - Shtennikov, V.N.; Budai, B.T. (Металлофизика и новейшие технологии, 2013)
Sometimes, the operations of electronic devices have failures due to lack of strength and ductility of the metal solder joints. As known, a main condition for ensuring of the required strength and ductility of the metal compounds is the choice of optimal brazing temperature. As the result of theoretical and experimental studies, the dependences connecting the surface temperature of joint metals and alloys with the parameters of the wave, laser, convection soldering are obtained. The use of the mentioned relationships increases the efficiency of fabrication of strength and ductile solder joints. При експлуатації електронних приладів іноді виникають відмови через недостатню міцність і пластичність паяних металевих з’єднань. Відомо, що основною умовою забезпечення необхідної міцности та пластичности металевих з’єднань є вибір оптимальної температури пайки. В результаті теоретичних і експериментальних досліджень одержано залежності, що зв’язують температуру поверхні металів і стопів, які з’єднуються, з параметрами хвильової, лазерної, конвекційної пайки. Застосування цих залежностей уможливило підвищити ефективність технології випуску міцних і пластичних з’єднань. При эксплуатации электронных приборов иногда возникают отказы из-за недостаточной прочности и пластичности паяных металлических соединений. Известно, что основным условием обеспечения требуемой прочности и пластичности металлических соединений является выбор оптимальной температуры пайки. В результате теоретических и экспериментальных исследований получены зависимости, связывающие температуру поверхности соединяемых металлов и сплавов с параметрами волновой, лазерной, конвекционной пайки. Применение упомянутых зависимостей позволило повысить эффективность технологии выпуска прочных и пластичных паяных соединений.